Poética do cinema infantil brasileiro : aspectos temáticos, formais e mercadológicos em Menino maluquinho - Ou, Mirian (Universidade Federal de São Carlos, 2012)
This work focuses on children's films and aims to raise some of their thematic, aesthetic and commercial characteristics. To do so, takes as its starting point the poetics of cinema as defined by Bordwell (2007) and analyzes two Brazilian films: The nutty boy a film (Helvécio Ratton, 1994) and The nutty boy 2 (Fernando Meirelles and Fabrizia Alves Pinto, 1998).
Keywords: Cinema; Filmes infantis; Cinema brasileiro; Crianças; Comunicação audiovisual; Mercado cinematográfico; Menino maluquinho; Poética; Brazilian cinema; The nutty boy; Poetics; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA